The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/ajmg.a.33474
|View full text |Cite
|
Sign up to set email alerts
|

Newborn and carrier screening for spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA) is a common autosomal recessive neuromuscular disorder caused by mutations in the survival motor neuron (SMN1) gene, affecting approximately 1 in 10,000 live births. The homozygous absence of SMN1 exon 7 has been observed in the majority of patients and is being utilized as a reliable and sensitive SMA diagnostic test. Treatment and prevention of SMA are complementary responses to the challenges presented by SMA. Even though a specific therapy for SMA is not currently available, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(158 citation statements)
references
References 37 publications
4
143
0
Order By: Relevance
“…Twenty‐seven healthy infants were enrolled within 12 months; 26 infants with SMA were enrolled concurrently over 22 months. Confirmation of the SMN1 exon 7 deletion and SMN2 copy number were performed as previously described 21. In addition, DNA from SMA subjects was screened for the SMN2 gene positive modifier mutation c.859G>C 22…”
Section: Methodsmentioning
confidence: 99%
“…Twenty‐seven healthy infants were enrolled within 12 months; 26 infants with SMA were enrolled concurrently over 22 months. Confirmation of the SMN1 exon 7 deletion and SMN2 copy number were performed as previously described 21. In addition, DNA from SMA subjects was screened for the SMN2 gene positive modifier mutation c.859G>C 22…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, despite the high carrier frequency, the incidence of spinal muscular atrophy is lower than expected. This finding may reflect that some fetuses have a 0/0 SMN1/SMN2 genotype (i.e., no SMN protein is present at all), which is known in other species to be embryonic lethal [10].…”
Section: Epidemiologymentioning
confidence: 99%
“…The potential for newborn screening of spinal muscular atrophy has been of great interest because the ideal time to initiate therapy would precede the initial degeneration of motor neurons, and newborn screening may help identify presymptomatic individuals [10,39]. Swoboda et al performed a prospective study in prenatally diagnosed infants with type I spinal muscular atrophy and found that, associated with the initial onset of signs or decline in function in these young infants, electrophysiologic evidence of precipitous denervation was detected (assessed with serial measurements of compound motor action potential amplitude and motor unit number estimation), suggesting that motor neuron loss occurs very early [56].…”
Section: Newborn Screeningmentioning
confidence: 99%
“…It has been postulated that this may reflect that some fetuses have a 0/0 SMN1/SMN2 genotype (ie, no SMN protein is present at all), which is known in other species to be embryonic lethal. 11 …”
Section: Epidemiologymentioning
confidence: 99%